2004
DOI: 10.1111/j.1748-0361.2004.tb00029.x
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Access to Care Among Rural Working‐age Adults

Abstract: A comprehensive approach to the health needs of rural working age adults must consider the unique characteristics of rural communities and populations, requiring cultural as well as financial creativity in the design of health delivery systems. The importance of resources such as education and employment points to the need to link health problems to area-specific rural economic development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 33 publications
0
39
0
Order By: Relevance
“…Minority populations within the USA tend to fare worse in such social determinants. This is true for educational attainment ( [26][27][28], p. 5), health literacy [29], income ( [27], p. 13), and poverty rates [30]. Differences in wealth between racial and ethnic groups are closely tied to disparities in self-reported health [31].…”
Section: Social Determinants Of Healthmentioning
confidence: 99%
“…Minority populations within the USA tend to fare worse in such social determinants. This is true for educational attainment ( [26][27][28], p. 5), health literacy [29], income ( [27], p. 13), and poverty rates [30]. Differences in wealth between racial and ethnic groups are closely tied to disparities in self-reported health [31].…”
Section: Social Determinants Of Healthmentioning
confidence: 99%
“…21 Geographic areas with high concentration of Blacks (focal and surrounding areas) have greater occupational and wage disparities between Blacks and Whites. 22 Disadvantage is both a collective and a contextual effect: geographic units surrounded by other units with high Black concentrations tend to be in the South, a less supportive institutional environment. Institutional effects, measured at the state level, also affect occupation and wage outcomes.…”
Section: Rural Racial/ethnic Minorities: Concentrated In the South Anmentioning
confidence: 99%
“…Further, despite identification of differences on some factors, the disparity has not been reduced (Glover, Moore, Probst, & Samuels, 2004). This study advances the current research by building classification models to identify those belonging to each groupthose that do and those that do not have healthcare coverage.…”
Section: Introductionmentioning
confidence: 88%
“…Many studies have found that females are less likely to be insured than males (Hendryx et al, 2002;Holtz-Eakin, 2002;Monheit & Vistnes, 2000), though the opposite has also been found (Carrasquillo, Himmelstein, Woolhandler, & Bor, 1999;Nelson, Bolen, Wells, Smith, & Bland, 2004). Race or ethnicity may also be a factor contributing to healthcare coverage disparity (Carrasquillo et al, 2000;Lucas, Barr-Anderson, & Kington, 2003;Monheit & Vistnes, 2000), with minorities generally having less healthcare coverage (Carrasquillo et al, 1999;Glover et al, 2004;Monheit & Vistnes, 2000). According to the results of multiple studies, those with lower incomes are less likely to have healthcare coverage (Cardon & Hendel, 2001;Carrasquillo et al, 1999;Lucas et al, 2003), and having healthcare coverage also has a relationship with employment status (Schmidt & Deichert, 1996) and type of employment (Krieger, Barbeau, & Soobader, 2005).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation